IMPLEMENTASI PELAYANAN KESEHATAN TERHADAP PASIEN PENGGUNA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT UMUM DAERAH KOTA CILEGON - Ardiansyah Ardiansyah; Sulasno Sulasno (NIAGARA Scientific Journal, 2017)
The low health status of underprivileged communities is caused by limited access to health services due to geographical constraints and cost barriers. Apart from that, community behavior that does not support a clean and healthy lifestyle is also an obstacle for the government to advance community development, especially in the health sector. Health efforts, especially in changing behavior, must be more of a bottom-up approach based on the needs and socio-cultural conditions of the local community. The method used in this research is a qualitative research method. Supporting factors include resources, communication between implementing agencies, social, economic and political environment, and policy standards and targets. Meanwhile, the inhibiting factor is the performance of policies that are still not in accordance with what is expected, especially the supply of drugs that are still incomplete.